Elaboration of the Model for the Assessment of Outdoor Advertising Effectiveness - Pilelienė, Lina; Grigaliūnaite, Viktorija (Journal of Emerging Trends in Marketing and Management, 2016)
Outdoor advertising is an inseparable part of a contemporary urban environment. Many companies consider it as one of the inevitable consumer attention grabbers. However, the intensifying speed of life and information overload stimulate the processes of adaptation and perceptual defense. Considering the growing competition among advertisers, the determination of the external factors affecting the effectiveness of outdoor advertising becomes an important issue. This study aims at elaborating the model for the assessment of outdoor advertising effectiveness which would enable the optimal choice of the place for the advertisement. The model is elaborated in stages: 1. The environmental factors possibly affecting the effectiveness of the outdoor advertising are determined based on the analysis of previous scientific researches; 2. The theoretical model for the assessment of outdoor advertising effectiveness is composed; 3. The theoretical model for the assessment of outdoor advertising effectiveness is being verified providing a questionnaire research (Structural equation modeling (SEM) using partial least squares (PLS) path modeling methodology is applied for statistical analysis); 4. The impact of model’s variables on advertising effectiveness is determined; 5. General model for the assessment of outdoor advertising effectiveness is composed. The research reveals that based on the specific situation the most important factors are those related to the place of dislocation; furthermore, factors influencing audience’s physical and psychological status and environmental conditions must be taken into consideration in order for the advertising to be visible for the target audience and have a possibility to become effective.